Characterisation (and mischaracterisation) of occupational injuries in Portuguese jurisprudence. An analysis from 2011 to 2021 - Rebelo, G.; Almeida, A. R. (Archivos de Prevención de Riesgos Laborales, 2024)
Based on Portuguese case law, this study examined the characterisation and mischaracterisation of occupational injuries in the Portuguese court system. A content analysis was carried out, namely on how the Portuguese courts understand the characterisation and mischaracterisation (requirements) of occupational injury sentences. Case law was collected and analysed from listed decisions by the higher courts (Supreme Court of Justice and the Portuguese Courts of Appeal), between 2011 and 2021. A total of 330 judicial decisions were identified and analysed; groups of descriptors were categorised and sub-themes were identified. The sub-theme ‘concept and scope of the injury’ was identified in 80 decisions and ‘mischaracterisation of injuries’ in 46 decisions. This analysis reflects the Portuguese courts' understanding of the extent to which occupational injuries are characterised, which will be important to safeguard the system of compensation for occupational injuries in Portugal.